2020
DOI: 10.1029/2020jd032384
|View full text |Cite
|
Sign up to set email alerts
|

Microphysical and Transportive Contributions to Normal and Anomalous Polarity Subregions in the 29–30 May 2012 Kingfisher Storm

Abstract: A developing supercell storm on 29–30 May 2012 in north‐central Oklahoma was observed with the Oklahoma Lightning Mapping Array (OKLMA) and three mobile radars. The storm's vertical charge structure inferred from the OKLMA was anomalous overall but varied considerably even within 10 km of the bounded weak echo region (BWER) and the bounded weak lightning region (BWLR) or lightning hole. Near the BWER, three distinct charge structures were observed—an inverted dipole, an inverted tripole, and a bottom‐heavy nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 83 publications
(227 reference statements)
0
6
0
Order By: Relevance
“…Therefore, the most likely region of positive charging of riming hydrometeors did not strictly coincide with storm maximum updraft speeds, as similarly observed by Chmielewski et al. (2020), and it is not suggested that the ACSs arose because of these elevated maximum updrafts. Rather, these updrafts may have been influenced by conditions that either more directly contributed to or were related to ACS development.…”
Section: Discussion On Proposed Contributions To Anomalous Chargingmentioning
confidence: 65%
See 3 more Smart Citations
“…Therefore, the most likely region of positive charging of riming hydrometeors did not strictly coincide with storm maximum updraft speeds, as similarly observed by Chmielewski et al. (2020), and it is not suggested that the ACSs arose because of these elevated maximum updrafts. Rather, these updrafts may have been influenced by conditions that either more directly contributed to or were related to ACS development.…”
Section: Discussion On Proposed Contributions To Anomalous Chargingmentioning
confidence: 65%
“…At these temperatures, collisional NIC involving riming hydrometeors would have been inactive as a result of homogeneous freezing (although studies have shown that some amount of charging may occur in the absence of LWC, e.g., Dye & Bansemer, 2019;Emersic & Saunders, 2020;Mitzeva et al, 2006). Therefore, the most likely region of positive charging of riming hydrometeors did not strictly coincide with storm maximum updraft speeds, as similarly observed by Chmielewski et al (2020), and it is not suggested that the ACSs arose because of these elevated maximum updrafts. Rather, these updrafts may have been influenced by conditions that either more directly contributed to or were related to ACS development.…”
Section: Evaluation Of Updraft Structure Relative To Charging Hypotheses: Mixed-phase Updraftmentioning
confidence: 89%
See 2 more Smart Citations
“…Past wind retrievals using the SMART radars have elucidated the structure and evolution of supercell thunderstorms (Bela et al, 2018; Betten et al, 2018; Calhoun et al, 2013; Davenport et al, 2019; DiGangi et al, 2016; Fried et al, 2016; Huntrieser et al, 2016; Li et al, 2017; Skinner et al, 2011) and mesoscale convective systems (Barth et al, 2015; Geerts et al, 2017; Lund et al, 2009; Miller et al, 2020; Palucki et al, 2011). The relationship between radar observed kinematics and cloud electrification for both natural lightning (Biggerstaff et al, 2017; Bruning et al, 2010; Chmielewski et al, 2020; Kuhlman et al, 2009; MacGorman et al, 2008; Payne et al, 2010) and triggered lightning (Hare et al, 2016; Hill et al, 2013; MacGorman et al, 2015; Pilkey et al, 2013) has also been studied with SMART radar observations. Additionally, the boundary layer structure of landfalling TCs has been documented using SMART radars (Alford et al, 2020; Hirth et al, 2012; Knupp et al, 2006; Lorsolo et al, 2008), as has the existence of mesovortices along the inner edge of hurricane eyewalls (Alford et al, 2019b; Fernandez‐Caban et al, 2019).…”
Section: Introductionmentioning
confidence: 99%